Effect of different light transmittance paper bags on fruit quality and antioxidant capacity in loquat - Xu, Hong-xia; Chen, Jun-wei; Xie, Ming (Journal of the science of food and agriculture, 2010)
BACKGROUND: Bagging has been widely used to improve the commercial value of fruit. The purpose of this study was to evaluate the effects of different light transmittance paper bags on the quality and antioxidant capacity of loquat fruit. Two loquat cultivars, Baiyu and Ninghaibai (Eriobotrya japonica Lindl.), were used for materials. One-layered white paper bags (OWPB) with ~50% light transmittance and two-layered paper bags with a black inner layer and a grey outer layer (TGDPB) with ~0% light transmittance were used as treatments and unbagged fruits were used as the control (CK) in this experiment. Fruit quality was determined by physicochemical characteristics, the quantity of sugar, total phenolic, flavonoid, carotenoid and vitamin C. The antioxidant capacities of the methanol extracted from the pulp were tested using three different assays.RESULTS: The results showed that bagging decreased the weight of fruit but promoted the appearance of loquat fruits. The total sugar content in the fruit bagged with OWPB was higher than in controls and in fruit bagged with TGDPB. The total phenolic and flavonoid contents were decreased by both bagging treatments, with the lowest occurring in the fruit bagged with TGDPB. Bagging also decreased the total antioxidant capacity of the fruit pulp, which was again lower in TGDPB-treated fruits than in those bagged using OWPB. Correlation analysis showed a linear relationship between total antioxidant capacity and the content of total phenolic and flavonoid.CONCLUSION: The results showed that different light transmittance bags had different effects on fruit quality and antioxidant capacity. In particular, bags with low light transmittance (TGDPB) decreased the inner quality and total antioxidant capacity of loquat fruit. All results indicated that bagging with OWPB was more suitable for maintaining the quality of the loquat fruit than bagging with TGDPB. Copyright